Chasing endless summer - Andrews, V. C. (Virginia C.) (The Sutherland Series, 2024)
"After the tragic death of her mother and a long period of isolation under the thumb of a cruel grandfather, young Caroline Brady has little to hope for in her life in the foreboding Southerland mansion. Her only companion, her enigmatic cousin, Simon, may be a wolf in sheep's clothing and is not to be trusted. But when Caroline's estranged father suddenly resurfaces with news of a new wife and stepchildren in Hawaii that she'll finally be allowed to visit, Caroline dares to hope for a new, normal life. Desperate for her father's love, Caroline will do anything to stay in this new home. But her troublesome stepsister has other plans, and Caroline cannot tell who to trust and who to run from. Will her new stepbrother and stepsister be a light in her dark life, or will they blot out the last slivers of sun forever?"--